Pelatihan Inovasi Pengemasan Produk Sabun Cuci Piring Bernilai Jual Ekonomis bagi Pokdarwis Desa Sialang Buah Sumatera Utara - Nasution, Myrna Pratiwi; Pinem, Laura Juita; Hutasuhut, Ahmad Luthfi (Jurnal Pengabdian UNDIKMA, 2025)
This community service activity aims to enhance the packaging innovation of dishwashing liquid products by Pokdarwis (Tourism Awareness Group) in Sialang Buah Village, North Sumatera, to increase their economic value and marketability. The methods employed include training, mentoring, and technology implementation, focusing on new pouch plastic packaging designs and both digital and conventional marketing strategies. The results indicate an improvement in participants' knowledge and skills in determining the cost of goods sold (COGS), using packaging equipment, and marketing products through social media. With these innovations, the Starlight dishwashing liquid brand is expected to gain better competitiveness and serve as a sustainable funding source for Pokdarwis.